Abdominal angiostrongylosis in an African man: case study. - Baird, J; Neafie, R; Lanoie, L; Connor, D (1987)
A nodule removed from the cecum of a 25-year-old Zairian man contained a degenerated adult nematode. The surrounding tissue contained larvae and eggs in various stages of cleavage. Eggs and larvae were indistinguishable from those of Angiostrongylus costaricensis. These morphological features are described. The diameter and cuticle, and the anatomic location of the adult worm is consistent with A. costaricensis. The tissue reaction was chronic with granulomatous inflammation and numerous eosinophils. This is the first report of abdominal angiostrongylosis of a human in Africa.